Peritumoral macrophages recruit eosinophils to promote antitumor immune responses in breast cancer - Joseph Saglimbeni; Eduardo Esteva; Josue Canales; Oriana A. Perez; Anna Eichinger; William Huntley; Kamal M. Khanna; Igor Dolgalev; Natalie Klar; Sylvia Adams; Boris Reizis (Proceedings of the National Academy of Sciences, 2025)
Breast tumors harbor dynamic microenvironments, with multiple immune cell types playing opposing roles during tumor progression and/or response to therapy. Tumor-associated macrophages promote mammary tumorigenesis, whereas the role of mammary tissue macrophages (MTMs) remains incompletely understood. High-dimensional immunostaining of murine mammary tumor progression revealed that MTMs were localized in the peritumoral stroma and associated with eosinophils, which were previously shown to facilitate antitumor T cell responses. The depletion of MTMs accelerated tumorigenesis in both spontaneous and orthotopically transplanted mammary tumor models. Upon induction of a productive antitumor response via the depletion of regulatory T cells, MTMs assumed an alternatively activated state and expressed eotaxins, thereby attracting eosinophils to peritumoral regions. MTMs expressed the receptor for the alarmin IL-33, which induced both MTM activation and eosinophil recruitment. These results suggest that MTMs can sense IL-33 and recruit eosinophils to facilitate antitumor immunity, a mechanism that may operate during tumor progression and be further enhanced during productive antitumor responses.